Dependency and readiness of urban youth to utilize public transportations as their premier mode of transport - Dahalan, Dzuhailmi; Abdullah, Haslinda; Alby, Jeffrey Lawrence D'Silva; Ismail, Ismi Arif; Ahmad, Nobaya (Canadian Center of Science and Education, 2013)
The usage of public transportations in Malaysia declined from 34% at 1985 to 20% at 1997 and now only left 10-12% (JICA, 1999). The government has targeted an increment of 2.5 times the number of users of public transportation in the Klang Valley, from estimated 240,000 passengers per day to 600,000 passengers in 2012. Such declination raises the question to which extent users really need public transportations? At the same time, to what extent targeting increment in statistic endeavor the readiness of users to utilize public transportations as their premier mode of transport? Secondary data analysis found that youth are potential user group to be significant contributors to achieve national statistical target. Hence, this paper discusses conceptually about to which extent dependency and readiness of urban youth to utilize public transportations as their premier mode of transport. This paper also implies that scientific exploration should be carry out to understand the dependency and readiness of urban youth to utilize public transportations as their premier mode of transportation.